2005
DOI: 10.1207/s15327078in0702_4
|View full text |Cite
|
Sign up to set email alerts
|

The Developmental Trajectory of Nonadjacent Dependency Learning

Abstract: We investigated the developmental trajectory of nonadjacent dependency learning in an artificial language. Infants were exposed to 1 of 2 artificial languages with utterances of the form [aXc or bXd] (Grammar 1) or [aXd or bXc] (Grammar 2). In both languages, the grammaticality of an utterance depended on the relation between the 1 st and 3rd elements, whereas the intervening element varied freely. High variability of the middle element is known to contribute to perception of nonadjacent dependencies (Góomez, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
342
3
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(372 citation statements)
references
References 28 publications
23
342
3
2
Order By: Relevance
“…Based on these findings, Santelmann and Jusczyk (1998) suggested that increases in infants' working memory capacity support an enhanced ability to detect nonadjacent structure. Gomez & Maye (2005) found further evidence of developmental differences in the ability to learn nonadjacent relationships. They found that 15-and 17-month-old infants were able to track nonadjacent relationships in an artificial language, while 12-montholds were unable to do so.…”
Section: Infant Experimentsmentioning
confidence: 76%
See 3 more Smart Citations
“…Based on these findings, Santelmann and Jusczyk (1998) suggested that increases in infants' working memory capacity support an enhanced ability to detect nonadjacent structure. Gomez & Maye (2005) found further evidence of developmental differences in the ability to learn nonadjacent relationships. They found that 15-and 17-month-old infants were able to track nonadjacent relationships in an artificial language, while 12-montholds were unable to do so.…”
Section: Infant Experimentsmentioning
confidence: 76%
“…the sentence "The boy is running" is grammatical, but "The boy can running" is not) if they are separated by no more than 3 morphemes (Santelmann & Jusczyk, 1998). Gomez and Maye (2005) found that 15-month-olds, but not 12-month-olds, were able to learn similar nonadjacent relationships when exposed to simpler language materials.…”
Section: Discussion Of Infant Experimentsmentioning
confidence: 96%
See 2 more Smart Citations
“…Other verb bias alternations such as the noun phrase/sentence complement alternation (e.g., the man wrote [that] the story [was interesting]; Garnsey, Pearlmutter, Myers & Lotocky, 1997) also involve variability in the post-verbal position (e.g., optional that), suggesting that such variation may play a role in verb class acquisition more generally. Humans also find it difficult to learn non-adjacent dependencies in artificial grammar learning tasks and variation can modulate this ability (Gómez, 2002;Gómez & Maye, 2005;Newport & Aslin, 2004). This is particularly relevant given that SRN models provide some of the best accounts of learning in these tasks (Chang, Janciauskas & Fitz, 2012).…”
Section: Discussionmentioning
confidence: 99%